2017
DOI: 10.1080/09593330.2017.1407828
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized landfill leachate treatment using Guadua amplexifolia bamboo as a source of activated carbon: kinetics study

Abstract: In the present study, the characteristics of leachate generated from dumpsite called 'Zapote' located in southern region of Tamaulipas, Mexico were evaluated. The adsorption of non-biodegradable organic matter measured as chemical oxygen demand (COD), color and heavy metals from leachate on activated carbon (AC) prepared in acid media from Guadua amplexifolia bamboo has been studied. In addition, the computation of kinetic parameters during the adsorption process as well as the most probable mechanisms was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 73 publications
0
0
0
Order By: Relevance
“…These suggest that the greater the dilution (or concentration decrease) of the LLCH, the better the elimination of color and nitrogen content [72]. Furthermore, the effectiveness of biochar in removing contaminants such as nitrogen from landfill leachate has also been demonstrated [77]. Additionally, studies have shown that the adsorption capacity of biochar increases from increasing the initial concentration of nitrogen or other contaminants in the solution [78].…”
Section: Adsorption Test Results For Biochar On Landfill Leachatementioning
confidence: 99%
“…These suggest that the greater the dilution (or concentration decrease) of the LLCH, the better the elimination of color and nitrogen content [72]. Furthermore, the effectiveness of biochar in removing contaminants such as nitrogen from landfill leachate has also been demonstrated [77]. Additionally, studies have shown that the adsorption capacity of biochar increases from increasing the initial concentration of nitrogen or other contaminants in the solution [78].…”
Section: Adsorption Test Results For Biochar On Landfill Leachatementioning
confidence: 99%
“…Sanitary landfill leachate (SLL) is extensively generated in sanitary landfills [1] as a result of rainwater infiltrating the disposed solid waste, which undergoes biological and physicochemical decomposition, as well as its inherent moisture content [2]. SLL is a darkcolored heterogeneous mixture [3,4] consisting of high concentrations of organic matter quantified as chemical oxygen demand (COD), heavy metals, chlorinated organic and inorganic salts, and extremely high concentrations of ammonium nitrogen (NH 4 + -N) [2,5,6]. The improper operation of a sanitary landfill, including leachate collection and treatment, poses serious risks to nearby surface waters, surrounding soils and groundwater [2,7].…”
Section: Introductionmentioning
confidence: 99%